Daddy Leave: Does It Change the Gender Division of Domestic Work? - Pia S. Schober (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
How to best provide incentives for a more gender-equal division of domestic work has entered policy debates in many Western countries. Growing evidence suggests that a gender-traditional division of household labor may result in lower fertility rates and greater risk of relationship breakdown and correlates with gender employment and wage gaps. Partly in response, many European countries have implemented some individual parental leave entitlements for fathers, which are not transferrable to mothers. Such non-transferable entitlements for fathers have been consistently shown to increase take-up of (short) leaves by fathers. Whether leave take-up indeed increases fathers' involvement in child care and housework also in the long-term is a more contested question. This DIW Roundup describes potential mechanisms that may underlie such a change and provides an overview of the existing evidence. Overall, previous studies from different countries point to some longer-term effects of fathers taking more than a couple of weeks of leave on a more equal gender division of domestic work.
Keywords: 330